REPRESENTASI KASUS KORUPSI AKIL MOCHTAR DALAM KARIKATUR PADA HEADLINE HARIAN PAGI RIAU POS (ANALISIS SEMIOTIK CHARLES SANDERS PEIRCE) - Panjaitan, Jimmy Ricardo; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Chairman of the Constitutional Court Akil Mochtar caught red-handed by the Anti-Corruption Commission while accepting bribes related to disputed local elections in several regions in Indonesia. This case is the most horrendous events in the history of fighting corruption and the arrest of the highest state officials have ever done KPK. The judges Jakarta Corruption Court finally decided life sentence due to Akil Mochtar found guilty of corruption and money laundering related to the handling of election disputes in the Constitutional Court. In reporting cases of corruption Akil Mochtar, Daily Morning Post Riau uses caricature to package this information in the headline. As one visual communication, a caricature is an interpretive picture that uses symbols to convey a message quickly and concisely, or something attitude toward people, situations, or specific events. The purpose of this study to determine how the corruption cases Akil Mochtar Representation in caricature on Headline Riau Pos daily morning by looking at the signs contained in caricature.This study used a qualitative descriptive method with semiotic analysis of meaning Charles Sanders Peirce elements Sign, object, and interpretant. Number of caricatures in the analysis of 3 pieces caricature of corruption headline Akil Mochtar edition October 2013 to July 2014 Data was collected using interviews, documentation, and literature.In this study the authors find meaning in the third image analyzing this caricature, sure: First, Abraham Samad Sign dressed in Roman warriors Object Abraham Samad has the courage to solve cases of corruption without fear and trembling interpretant Abraham Samad managed to catch the perpetrators of corruption that exist in Indonesia. Secondly, Sign Akil Mochtar, who is always asking for money in a local election dispute Object Akil Mochtar has damaged public confidence in the Indonesian Constitutional Court interpretant All winning regional head for money in the Constitutional Court. Third, Akil Mochtar Sign lay helpless and bound iron chain in Object Akil Mochtar verdict of life imprisonment and can not do anything else interpretant sentence of life imprisonment was proper because it has damaged the image of the Constitutional Court which had long been believed.Key word : Representation, Corruption Cases, Caricature